Long-term complete response with third-line PARP inhibitor after immunotherapy in a patient with triple-negative breast cancer: a case report - Caputo, Roberta; Pagliuca, Martina; Pensabene, Matilde; Parola, Sara; De Laurentiis, Michelino (Frontiers in Oncology, 2023)
While standard treatment has shown efficacy in patients with breast cancer gene (BRCA) mutations, recurrence rates are high and additional effective therapies are needed. Olaparib, a poly adenosine diphosphate–ribose polymerase (PARP) inhibitor, approved for the treatment of metastatic germline BRCA1/BRCA2 breast cancer (BC), has demonstrated evidence of a progression-free survival (PFS) benefit, good safety profile, and improved quality of life compared with standard chemotherapy. We here describe the case of a patient with BRCA1 mutated advanced BC and a long history of response to chemotherapy and immunotherapy who received systemic treatment with olaparib. First diagnosed in March 2011 at the age of 38 years with early-stage BC of the right breast, she underwent quadrantectomy plus ipsilateral axillary lymphadenectomy and adjuvant treatments with chemotherapy regimen containing 5-fluorouracil, epirubicin, and cyclophosphamide (FEC) followed by radiotherapy. Five years later, following a contralateral nodule detection leading to left breast quadrantectomy, she received adjuvant systemic treatment with docetaxel plus cyclophosphamide and radiotherapy. Gene testing showed a germline BRCA1 deleterious variant, and she underwent bilateral prophylactic mastectomy and oophorectomy. One year later, skin metastasis and bone infiltrations were detected, and she was started on first-line systemic treatment. The patient was enrolled in the IMpassion131 trial (investigating atezolizumab addition to paclitaxel) but unblinding showed that she was randomized in the placebo arm. She received second-line systemic therapy with LAG525 plus carboplatin (CLAG525B2101 trial) resulting in a PFS of 14 months. At disease progression, she was eligible for systemic third-line therapy with olaparib (300 mg twice daily) and had a complete response after 6 months of therapy and a PFS of 40 months at the time of writing. To the best of our knowledge, this is the first report of a complete response following treatment with third-line systemic olaparib in a long-responding patient and relatively good tolerability and quality of life, pre-treated with both chemotherapy and immunotherapy.